JAPAN'S FOREIGN POLICY ON MIGRANT WORKERS: IMPLEMENTATION OF THE SPECIFIED SKILLED WORKERS (SSW) POLICY IN OVERCOMING LABOR CRISIS - Febie Nur Arief (UNIDA GONTOR, 2022)
This study discusses the immigration policies implemented by Japan’s governmentto overcome labor problems. This study aims to analyze Japan's demographicconditions through the concept of human capital, as well as analyze the SpecifiedSkilled Workers (SSW) policy implemented by the Japanese government as an effortto deal with demographic problems in the country through the concept of foreignpolicy. There are 4 variables in the concept of foreign policy, namely: the reasons forforming the policy (Input), the strategy for implementing the policy (Process), theinterests to be achieved in the policy (Output), and the impact of implementing thepolicy (Outcome). Using a qualitative method with an exploratory approach, this studyshows that Japan is facing a labor crisis, so the Japanese government makes policiesrelated to the acceptance of foreign workers to fill the workforce vacancies in sectorsthat require skilled and expert workers. Japan cooperates with 14 to bring in foreignworkers based on their skills and expertise.